Cause, catalyst or conjunction? The influence of the Habitats Directive on policy instrument choice in Member States. Issue 6 (3rd June 2017) - Bouwma, Irene; Arts, Bas; Liefferink, Duncan
Abstract : In the process of implementing EU policy, Member States sometimes introduce new policy instruments in cases where this is not obligatory. To better understand this phenomenon, this paper reviews three cases in which new instruments emerged and develops a methodology to trace back the influence of EU Directives on instrument choice. The method is illustrated by a narrative of the emergence of new management planning instruments during the implementation of the EU Habitats Directive in three EU Member States: Finland, Hungary and the Netherlands. Three key features of a policy instrument are defined, namely, its authoritative force, action content and governance design. These are used to measure the contribution of the Habitats Directive compared to other potential explanatory causes for the emergence of the new policy instrument. In all three reviewed countries a nested causal relationship between the Habitats Directive and the introduction of the new policy instrument is identified. Based on the relative contribution of the Habitats Directive to the emergence of the new instrument a distinction is made whether the Directive acted as a cause, catalyst or if conjunction occurred.